2016
DOI: 10.1186/s13041-016-0215-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of LRRK2 promoter activity and gene expression by Sp1

Abstract: BackgroundThe dopaminergic neurodegeneration in the nigrostriatal pathway is a prominent neuropathological feature of Parkinson’s disease (PD). Mutations in various genes have been linked to familial PD, and leucine-rich repeat kinase 2 (LRRK2) gene is one of them. LRRK2 is a large complex protein, belonging to the ROCO family of proteins. Recent studies suggest that the level of LRRK2 protein is one of the contributing factors to PD pathogenesis. However, it remains elusive how LRRK2 is regulated at the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 87 publications
3
21
0
Order By: Relevance
“…A previous study identified potential transcription factors of LRRK2 and noted that Sp1 can regulate the promoter activity and gene expression of LRRK2. 40 The mRNA and protein expression levels of Sp1 showed the same trend as the expression levels of LRRK2 in this study; VIP (1, 10, or 50 μM) promoted the mRNA and protein expression levels of Sp1 in HUVECs (Figs. 5A, 5D).…”
Section: Vip Promotes the Mrna And Protein Expression Of Sp1 In Huvecsupporting
confidence: 76%
See 3 more Smart Citations
“…A previous study identified potential transcription factors of LRRK2 and noted that Sp1 can regulate the promoter activity and gene expression of LRRK2. 40 The mRNA and protein expression levels of Sp1 showed the same trend as the expression levels of LRRK2 in this study; VIP (1, 10, or 50 μM) promoted the mRNA and protein expression levels of Sp1 in HUVECs (Figs. 5A, 5D).…”
Section: Vip Promotes the Mrna And Protein Expression Of Sp1 In Huvecsupporting
confidence: 76%
“…According to the transcription factor binding sites of the LRRK2 gene, a previous study identified several putative transcription factors for LRRK2, including Sp1, GATA1/2, AP-1, HNF-3α, and NF-AT1. 40 In this study, we evaluated the changes in RNA expression after the application of VIP to HUVECs and found that Sp1 showed the most significant positive changes, indicating that VIP can positively regulate the RNA expression of Sp1. In addition, a previous study also confirmed that Sp1 is able to regulate the promoter activity and gene expression of LRRK2.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Some research had discovered that the expression of SP1 was increased in the brains of patients or models with AD, PD or other neurodegenerative disorders . A prior study also noted that SP1 signalling was significant in ameliorating the neuropathological changes involving PD by the manipulation of LRRK2 . In addition, some studies also demonstrated that SP1 participated in modulating inflammatory response in diverse diseases .…”
Section: Discussionmentioning
confidence: 99%